Structural organization of the corpus callosum predicts attentional shifts after continuous theta burst stimulation - Chechlacz, Magdalena; Humphreys, Glyn W.; Sotiropoulos, Stamatios N.; Kennard, Christopher; Cazzoli, Dario (Society for Neuroscience, 2015)
Repetitive transcranial magnetic stimulation (rTMS) applied over the right posterior parietal cortex (PPC) in healthy participants has been shown to trigger a significant rightward shift in the spatial allocation of visual attention, temporarily mimicking spatial deficits observed in neglect. In contrast, rTMS applied over the left PPC triggers a weaker or null attentional shift. However, large interindividual differences in responses to rTMS have been reported. Studies measuring changes in brain activation suggest that the effects of rTMS may depend on both interhemispheric and intrahemispheric interactions between cortical loci controlling visual attention. Here, we investigated whether variability in the structural organization of human white matter pathways subserving visual attention, as assessed by diffusion magnetic resonance imaging and tractography, could explain interindividual differences in the effects of rTMS. Most participants showed a rightward shift in the allocation of spatial attention after rTMS over the right intraparietal sulcus (IPS), but the size of this effect varied largely across participants. Conversely, rTMS over the left IPS resulted in strikingly opposed individual responses, with some participants responding with rightward and some with leftward attentional shifts. We demonstrate that microstructural and macrostructural variability within the corpus callosum, consistent with differential effects on cross-hemispheric interactions, predicts both the extent and the direction of the response to rTMS. Together, our findings suggest that the corpus callosum may have a dual inhibitory and excitatory function in maintaining the interhemispheric dynamics that underlie the allocation of spatial attention.